2006
DOI: 10.1302/0301-620x.88b2.17065
|View full text |Cite
|
Sign up to set email alerts
|

Ankle arthrodesis and its relationship to ipsilateral arthritis of the hind- and mid-foot

Abstract: It has been suggested that arthrodesis of the ankle leads to osteoarthritis of the joints of the ipsilateral hind- and midfoot. We believe these studies overlooked the presence of osteoarthritic changes in these joints before the arthrodesis. We reviewed the pre-operative radiographs of 70 patients with osteoarthritis of the ankle who underwent 71 ankle arthrodeses (one was bilateral). The talonavicular, calcaneocuboid, subtalar and naviculocuneiform joints were given an osteoarthritis score according to Kellg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 8 publications
(8 reference statements)
2
43
0
Order By: Relevance
“…During the followup period, we observed development of arthritis at the subtalar joint in 16.6% and at the talonavicular joint in 11.1% of patients and progression of preexisting arthritis 30% and 19%, respectively. Our observations confirm those of Sheridan et al [43] who reported a high percentage (96%) of subtalar and midfoot arthritis was preexisting due to ankle malfunction in end-stage arthritis. Progression of preexisting arthritis has been reported in between 0 and 70% [5,27,30,48].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…During the followup period, we observed development of arthritis at the subtalar joint in 16.6% and at the talonavicular joint in 11.1% of patients and progression of preexisting arthritis 30% and 19%, respectively. Our observations confirm those of Sheridan et al [43] who reported a high percentage (96%) of subtalar and midfoot arthritis was preexisting due to ankle malfunction in end-stage arthritis. Progression of preexisting arthritis has been reported in between 0 and 70% [5,27,30,48].…”
Section: Discussionsupporting
confidence: 92%
“…Long-term studies with followup of more than 20 years revealed a high percentage (ie, 47% to 100%) of arthritis at the adjacent joints [11,17,51]. However, only few studies reported the amount of preexisting arthritis of these joints [5,27,43,48] and the clinical relevance of radiographic signs of arthritis is not entirely clear [4,37,51].…”
Section: Introductionmentioning
confidence: 99%
“…It also highlights that following AA there is an increased mobility in the ipsilateral transverse tarsal and subtalar joints which plays an important role in compensating for a stiff ankle. This compensatory movement is thought to lead to an increased incidence of arthrosis of the mid or hindfoot and is seen in up to 95.8% of patients with ankle OA, with the subtalar joint being the most commonly and severely affected [13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether the adjacent joint degeneration was associated with patient's competent symptoms still lacked sufficient evidence. Nevertheless, it was clear that placing the ankle fusion in the coronal neutral position with coronal plane mildly exhibiting valgus might reduce the chance of adjacent joint degeneration 27,28) . …”
Section: Discussionmentioning
confidence: 99%